One-Way Accumulators: A Decentralized Alternative to Digital Signatures - Benaloh, Josh; Mare, Michael de (Eurocrypt 93, 1993)
This paper describes a simple candidate one-way hash function which satisfies a quasi-commutative property that allows it to be used as an accumulator. This property allows protocols to be developed in which the need for a trusted central authority can be eliminated. Space-efficient distributed protocols are given for document time stamping and for membership testing, and many other applications are possible.